2012
DOI: 10.1111/j.1750-3841.2012.02886.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidants in Purple Sprouting Broccoli under Mediterranean Climate

Abstract: The results of this study reported data of the health-promoting nutrients and natural antioxidants of EEP, EP, and LP purple sprouting broccoli varieties grown under the Mediterranean climate. The vitamin C, phenolic compounds, and glucosinolates in these purple varieties were higher than in traditionally grown green broccolis and other purple broccolis grown under different climate conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
3
13
1
Order By: Relevance
“…As shown in Table mean values obtained for sprouting broccoli varieties are considerably higher for the majority of varieties in both years. Although few studies have been carried out reported levels of total phenolics measured using HPLC methods in leaf, stalk and floret of purple sprouting broccoli cultivars (‘Rudolf’, ‘Purple Sprouting’ or ‘Viola’) were considerably higher than values reported here and in the region 4–5000 mg 100 g −1 FW or 12–9900 mg 100 g −1 dry weight (DW) depending on the study …”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…As shown in Table mean values obtained for sprouting broccoli varieties are considerably higher for the majority of varieties in both years. Although few studies have been carried out reported levels of total phenolics measured using HPLC methods in leaf, stalk and floret of purple sprouting broccoli cultivars (‘Rudolf’, ‘Purple Sprouting’ or ‘Viola’) were considerably higher than values reported here and in the region 4–5000 mg 100 g −1 FW or 12–9900 mg 100 g −1 dry weight (DW) depending on the study …”
Section: Resultscontrasting
confidence: 72%
“…Green broccoli types are an important commercial crop and several studies have focussed on bioactive (glucosinolate and phenolic) content in varieties grown under uniform cultural conditions (reviewed by Reilly). A recent study examined bioactive content in three purple sprouting broccoli varieties (‘Rudolf’, ‘Purple Sprouting’ and ‘Late Purple Sprouting’ . A single purple sprouting variety ‘Viola’, ‘Bordeaux’ or ‘Purple Mountain’ has been included in a small number of studies for comparison purposes; however, to our knowledge no previous studies have evaluated bioactive content in a range of sprouting broccoli varieties grown under uniform cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC coupling with a mass spectrometer detector enhances selectivity and specificity [4], [9], [10], [12]. In addition, the use of chromatographic columns embedded with stationary phases seems to provide better resolution by improving chromatographic separation [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…5-Methyltetrahydrofolate was found as the predominant vitamer at each stage. Vitamin C, phenolic compounds, and glucosinolates in these purple sprouting varieties, EEP (Extra Early), EP (Early) and LP (Late) grown in Spain, were higher than in traditionally grown green broccolis and other purple broccolis grown under different climate conditions (Rodríguez-Hernández et al 2012 ).…”
Section: And Ohmentioning
confidence: 99%